CIVIL LAW AND UPHOLDING OF INDIVIDUAL RIGHTS IN MODERN CONDITIONS - Suleymenov Майдан Кунтуарович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article is devoted to the issue date that is the role of civil rights in ensuring the rights of individuals. Considerable attention is paid to the analysis of the research concerning interests of the individual held in the works of N.A. Shaikenov. The author reveals the problem of ensuring the rights of the individual in modern conditions, and comes to the conclusion that most of these rights (with the exception of political rights) in one degree or another are governed by civil law. The relationship between the concepts "interest" and "subjective right" is analyzed. In this case, if N.A. Shaikenov considered a subjective right as the main legal means of realizing the interest, author of the article comes to the conclusion that the meaning of the existence of a subjective right as a legal phenomenon is to give the individual an effective legal remedy in its public relations to meet the needs, to implement its interest, taken under state protection. The article reveals the concept of "individual rights", as well as an analysis of the views of researchers on the personal, political, socio-economic and cultural human rights in the modern conditions is made. The idea of abandoning the legal demarcation of individual rights to personal rights related and not related to property, as well as the division of rights and freedoms on the natural and "positive" is substantiated, as in the present conditions of division data lose their legal meaning. The author notes that in civil law the term "ensuring " is not used. Key terms are "preserving of civil rights" and "protection of civil rights." In this regard, the views of researchers on the relationship between the concepts of "preserving of rights" and "protection of the rights" are analyzed. The approach to the concept of "self-defense" enshrined in the Civil Code of the Republic of Kazakhstan is supported.